2009
DOI: 10.1007/s00253-009-2323-y
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of mushroom extracts on sucrose-dependent oral biofilm formation

Abstract: Mushrooms contain large quantities of alpha-glucans. Shiitake (Lentinula edodes), Japan's most popular edible mushroom, has been reported to contain about 6% (weight/dried weight) of alpha-(1,3)-glucan. This glucan is one of the major components of oral biofilm formed by the cariogenic bacteria Streptococcus mutans and Streptococcus sobrinus. We found that extracts from shiitake and other edible mushrooms could reduce preformed biofilms of S. mutans and S. sobrinus in the presence of dextranase. We also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…This value reveals the composition of the glucans, synthesized by the S. mutans. 8) The streptococcal glucan biofilms may be composed of approximately 60-70 mol% α-1,3-glucosidic linkages. 2,8,9) The catalytic preference of our presented enzyme for hydrolysis of biofilms was similar to that of mutanase of Trichoderma harzianum.…”
Section: Mutanase Of P Humicus From Fermented Food Hydrolyzed Insolumentioning
confidence: 99%
“…This value reveals the composition of the glucans, synthesized by the S. mutans. 8) The streptococcal glucan biofilms may be composed of approximately 60-70 mol% α-1,3-glucosidic linkages. 2,8,9) The catalytic preference of our presented enzyme for hydrolysis of biofilms was similar to that of mutanase of Trichoderma harzianum.…”
Section: Mutanase Of P Humicus From Fermented Food Hydrolyzed Insolumentioning
confidence: 99%
“…However, without targeting and reducing dental plaque, fluoride products are unable to completely inhibit dental caries (Fejerskov 2004). Natural products and derivatives, such as green tea catechins (Hirasawa et al 2006), cranberry constituents , Galla chinensis (Xie et al 2008), citrus lemon oil (Liu et al 2013), mushroom extracts (Yano et al 2010), and several bioactive macromolecules (Shang et al 2014;Lee and Park 2015), have been reported to be effective against the growth and adherence of S. mutans. In addition, small molecules, such as tt-farnesol (Koo et al 2003), walkmycin C (Eguchi et al 2011), and anthraquinones (Coenye et al 2007), have been shown to inhibit the growth of cariogenic bacteria, and even the development of caries, but few of these compounds target S. mutans biofilms.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…These microorganisms form biofilms on the tooth surface by attachment to the acquired pellicle on the enamel and adhesion to the tooth by cell to cell interactions. [20] The shiitake extracts could reduce preformed biofilms in the presence of dextranase which is a water-soluble α-(1,6)-linked glucan. This dextran degrading enzyme, dextranase, has been used in the treatment to reduce the formation of dental plaque.…”
Section: Introductionmentioning
confidence: 99%
“…This dextran degrading enzyme, dextranase, has been used in the treatment to reduce the formation of dental plaque. [20] An in vitro dental caries biofilm model was developed in combination with cariogenic microorganisms with dental hard tissue substratum (dentin or enamel) allowing modeling of frequent acid challenges by sucrose pulsing with a constant depth film fermentor. The amount of mineral loss quantifies anticariogenicity.…”
Section: Introductionmentioning
confidence: 99%